Efficient Regeneration of Human Vα24+ Invariant Natural Killer T Cells and Their Anti-Tumor Activity In Vivo. (1st August 2016) - Yamada, Daisuke; Iyoda, Tomonori; Vizcardo, Raul; Shimizu, Kanako; Sato, Yusuke; Endo, Takaho A.; Kitahara, Genta; Okoshi, Momoko; Kobayashi, Midori; Sakurai, Maki; Ohara, Osamu; Taniguchi, Masaru; et al.
Abstract: Reprogramming of antigen-specific T lymphocytes into induced pluripotent stem cells (iPSCs) and their subsequent re-differentiation has enabled expansion of functional T lymphocytes in vitro, thus opening up new approaches for immunotherapy of cancer and other diseases. In this study, we have established a robust protocol to reprogram human invariant NKT (Vα24 + iNKT) cells, which have been shown to act as cellular adjuvants and thus exert anti-tumor activity in mice and humans, and to re-differentiate the iNKT cell-derived iPSCs into functional iNKT cells. These iPSC-derived iNKT cells (iPS-Vα24 + iNKT cells) can be activated by ligand-pulsed dendritic cells (DCs) and produce a large amount of interferon-γ upon activation, as much as parental Vα24 + iNKT cells, but exhibit even better cytotoxic activity against various tumor cell lines. The iPS-Vα24 + iNKT cells possess significant anti-tumor activity in tumor-bearing mice and can activate autologous NK cells upon activation by ligand-pulsed DCs in the NOG mouse model in vivo, further extending their therapeutic potential. This study thus provides a first proof of concept for the clinical application of human iPS-Vα24 + iNKT cells for cancer immunotherapy. Abstract : We developed a protocol to reprogram human Vα24 + iNKT cells and to re-differentiate the iNKT cell-derived iPSCs into functional iNKT cells. The iPS-Vα24 + iNKT cells activated by murine DC/Gal produce a large amount of interferon-γ upon activation and exhibit even better cytotoxic activity against various tumor cell lines than parental Vα24 + iNKT cells. As a preclinical study, we show that the iPS-Vα24 + iNKT cells possess significant anti-tumor activity in tumor-bearing NOG mice and adjuvant activity for NK cells in vivo.